The issue of providing services in a private dental clinic - Kunkela, Josef (2018)
The dissertation critically studies the issue of providing services in private dentistry in order to find the most important factors influencing the quality of dental care and the possibility of their influence. The study is focused on the assessment of the value of provided dental care from the point of view of the patient. Emphasis was placed on these quality factors: access to the clinic's reception, access of dental staff, waiting time for treatment, wait time in the waiting room, helpfulness in solving the acute problem, painlessness of the procedure, functionality and durability of the procedure, overall environment of the clinic, in order to create added value for the patient.The research was supported by the analysis of the statistical data obtained from the patients of the private dental clinic. The analysis shows that the most important factors of quality of dental care are the functional and durability of the procedure, the friendliness of the current problem, the access of the medical staff and the painlessness of the procedure. An interesting finding is that the price for provided care is among the studied factors up to the 5th place. Equally important is the finding that obtaining feedback from patients appears to be very beneficial for the further development of the dental care facility and ensuring maximum patient loyalty.Another goal of the thesis was to establish operational quality standards for healthcare facilities, to assess the primary and supportive value-generating activities that are essential for creating added value for the patient as a pillar of loyalty. Creating and describing tools for the effectiveness of dental practice together with Best Practices has had the greatest impact in putting the results of the dissertation into practice. The dental software XDENT, which includes iKlient client zone, was designed and implemented.